Reflections on Schaefer-Hartshorne debate: A critique - Mumtaz Khan (National Geographical Journal of India, 2024)
Academic debate in a discipline is an important sign of a healthy academic environment. It is also one of the prerequisites for the growth of a discipline. The Schaefer-Hartshorne debate on the methodology and philosophy of geography, which took place in the 1950s, is easily the most important debate in the discipline till now. The debate centred around whether geography is a unique discipline that should focus on describing individual regions or formulating theories and laws concerning the location and distribution of phenomena in geographical space. At that time, this debate divided the entire geography community of the world into two academic camps. So much so the debate became personalised and acrimonious; nonetheless, this rich and enthralling debate has shaped the nature of geographical inquiry in many ways. Though much is written about this debate, this paper focuses on the non-academic and unethical practices of followers of Fred K. Schafer that contributed to the popularity of his point of view.